Redesigning Concept of the UIN Raden Intan Lampung’s Student Dormitory - Ahmad Jajuli; Ai Siti Munawaroh; Dadang Hartabela (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
The existence of a dormitory in the UIN Raden Intan Lampung is one of the supporting activities for lectures. Plus, the number of students who come from outside the city of Bandar Lampung makes the dormitory a very interesting place to live. Meanwhile, the dormitory capacity is still very limited. Therefore, it is necessary to redesign so that capacity can be increased, and student activities can be accommodated. This study aims to redesign the current student dormitory. The research method is carried out by documentation at the site location, analyzing the problems and resulting the concept. The results showed that there were three main concepts in redesigning the student dormitory of UIN Raden Intan Lampung, namely: site and environmental, building user and the building itself.